Determining Thermal Radiation from a Pool Fire Using Computational Geometry - Mohammad Seyfi (Chemical Engineering Transactions, 2025)
Determining the failure onset of an object due to incident thermal radiation from a fire has been a challenging topic in fire consequence analysis in the process safety industry. Failure of equipment exposed to fire is typically estimated using an uniform flame surface emissive power (SEP) in combination with atmospheric absorption and a view factor (configuration factor) which is usually determined based on the most conservative orientations and distances, namely the radiation target at the shortest distance and perpendicular to the incident radiation direction. The proposed method in this manuscript features a source-based representation of the view factor, as opposed to the conventional receiver-based view factors. This approach allows for a variable SEP instead of a uniform value for the entire flame region. The view factor is calculated using computational geometry, between individual segments of the radiation source and segments of the exposed object, based on analytical solutions of the view factor between finite surfaces. The total thermal radiation flux incident on each segment of the exposed object is thus calculated by summing the radiation from each fire segment using a separate SEP and view factor. To evaluate the proposed method with existing models, a simplified arrangement is considered. This involves a pool fire on the ground and a vertical cylindrical storage tank representing the exposed object. However, this method is applicable to a wide range of other spatial configurations, including multiple fire sources and exposed objects, as well as various shapes for flames or exposed objects.